A novel approach for seismoelectric measurements using multielectrode arrangements: II—Laboratory measurements. Issue 3 (21st June 2018) - Devi, M S; Garambois, S; Brito, D; Dietrich, M; Poydenot, V; Bordes, C
SUMMARY: Transient electrokinetic effects may generate conversions between seismic and electromagnetic energy in fluid-filled poroelastic media. Two resulting seismoelectric signals have been predicted and identified: on the one hand electric fields accompanying seismic waves and on the other hand electromagnetic disturbances generated when seismic waves are crossing interfaces. The coseismic electrical field is in general the dominant effect, but it only provides local information around the electrical receivers. On the contrary, the seismoelectric interface response could be exploited in a new high-resolution imaging technique, as it is particularly sensitive to fluid contrasts. However, the detection of such events is a challenging task, mainly because it is usually masked by the higher amplitude coseismic electric field and by the presence of strong electrical noise. In order to increase the signal-to-noise ratio of the interface response, we experimentally study the sensitivity of seismoelectric signals to various electrode arrangements used for their recording. For that, we use a filter theory approach to investigate the response of electrode arrays to measure seismoelectric signals. Then, we confront this approach with seismoelectric data acquired in homogeneous silica glass-beads in laboratory experiments. The measured laboratory coseismic signals were also successfully compared with numerical simulations, which in turn have been used to predict the sensitivity of the interface electromagnetic signals to the data acquisition configuration. This study demonstrates the possibilities offered by multielectrode arrays to enhance the electromagnetic interface response.